The immediate factor of tuberculin in the sanatorium treatment of pulmonary tuberculosis - Bruce, George Robert (The University of Edinburgh, 1914)
The present inquiry is restricted to one branch of the subject, namely the results on discharge, estimated as exactly as possible by several criteria, which were obtained by sanatorium treatment, combined with tuberculin, in a group of 137 cases of pulmonary tuberculosis. It is proposed to analyse the cases, according to the various stages of the disease, and to consider the results on discharge according to the following criteria; (1) the clinical results as estimated by the physical signs in the chest, and the general condition of the patient; (2) the presence or absence of tubercle bacilli (T.B.) in the sputum; (3) the amount of restoration of working power; (4) the average gain of weight. Special attention will be given to the consideration of cases, systemic on admission, i.e. those cases which showed signs of febrile or other constitutional disturbance. It has generally been maintained that such cases react with difficulty to any form of treatment, and more especially to tuberculin treatment. In fact many authorities go so far as to state that under no circumstance should systemic cases be given tuberculin. The results obtained in the cases,systemie on admission,will be compared with the results of the non - systemic cases, and with those of all cases taken together. Results which other observers have obtained both with and without tuberculin will be compared with the results obtained in this series. In addition, certain cases, in which the administration of tuberculin seemed to have a bearing, more or less evident in the results, whether for good or for evil, will be described more fully. A short description of the reaction, difficulties, and dangers met with in the course of the treatment will be given, but no theoretic al disquisition on the action of tuberculin will be undertaken, except such as is necessary to explain points of theory arising in the cases under consideration. The final results of tuberculin treatment can only be discovered by actuarial methods - e.g. by the consideration of the numbers alive, and in good health, after a certain number of years of different groups of cases, treated with and without tuberculin. This of course does not come within the scope of this inquiry.